2010
DOI: 10.2965/jwet.2010.363
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antiviral Drugs Oseltamivir Phosphate and Oseltamivir Carboxylate in Neya River, Osaka, Japan

Abstract: Presence of the antiviral drug oseltamivir in considerable concentrations in surface waters especially in seasonal and pandemic influenza cases has raised concerns on its possible consequences in the environment and human health. This investigation aimed to elucidate concentration levels of the drug in Neya River in Osaka during 2009/2010 seasonal influenza. Oseltamivir phosphate was detected for the first time in Neya River suggesting the presence of the drug in phosphate form in surface waters is significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 8 publications
4
28
1
1
Order By: Relevance
“…The highest OC concentrations detected in the environment to date (0.86 g/liter [18]) are lower than the lowest resistance-inducing concentration in the mallard model (0.95 g/liter [23]) but in the same order of magnitude. Furthermore, occasional peak concentrations may exceed detected levels, especially during pandemics, and different IAVs acquire resistance mutations at differ- ent OC exposure levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The highest OC concentrations detected in the environment to date (0.86 g/liter [18]) are lower than the lowest resistance-inducing concentration in the mallard model (0.95 g/liter [23]) but in the same order of magnitude. Furthermore, occasional peak concentrations may exceed detected levels, especially during pandemics, and different IAVs acquire resistance mutations at differ- ent OC exposure levels.…”
Section: Discussionmentioning
confidence: 93%
“…OC, the drug primarily studied, is inefficiently removed by conventional sewage water treatment (16,17). Consequently, OC can be discharged to water environments where waterfowl reside, and OC concentrations as high as 865 ng/liter have been detected in surface water (18)(19)(20). If avian IAV is exposed to OC in its natural host and acquires resistance, there is a risk that emerging human-pathogenic IAV strains carrying avian gene segments may be resistant (21).…”
mentioning
confidence: 99%
“…Moreover, Japan is at the top in per capita consumption of oseltamivir (Soderstrom et al, 2009). Detection of oseltamivir carboxylate (OC) in considerable concentrations in -58 -wastewaters and surface waters particularly in Kansai region of Japan has been reported in several occasions within the last ten years (Ghosh et al, 2010a and b;Takanami et al, 2010a). For the first time, we found oseltamivir phosphate (OP) in addition to its active metabolite OC in Neya River water in Osaka (Takanami et al, 2010a).…”
Section: Introductionmentioning
confidence: 91%
“…Widespread detection of antiviral drugs in wastewaters and surface waters particularly during seasonal and pandemic influenza cases (Bartels and Tumpling, 2008;Soderstrom et al, 2009;Prasse et al, 2010;Ghosh et al, 2010a and b;Takanami et al, 2010a), and their potential negative consequences to aquatic ecology and humans (Taylor et al, 2008;Straub, 2009) has recently attracted considerable attention from scientific communities. After administration, the drugs and their metabolites are excreted, carried away in sewers, passed through treatment facilities (Fick et al, 2007;Accinelli et al, 2007Accinelli et al, , 2010aAccinelli et al, , and 2010bSlater et al, 2011) and reached water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports about occurrence of oseltamivir and oseltamivir carboxylate in wastewater and river water of Japan and Europe at tens of ng L −1 to low μg L −1 levels (Azuma et al, 2012;Ellis, 2010;Fick et al, 2007;Ghosh et al, 2009;Leknes et al, 2012;Prasse et al, 2010;Soderstrom et al, 2009;Takanami et al, 2010). Prasse et al (2010Prasse et al ( , 2011 have also reported the presence of other antivirals, including acyclovir and its metabolite carboxy-acyclovir, zidovudine, lamivudine, abacavir, and penciclovir in wastewater, river water, and even groundwater in Germany.…”
Section: Introductionmentioning
confidence: 99%